A Novel Electrolytic Technique for Oxidation-Reduction - Karkare, S.M.; Edkie, R.G.; Madhava Rao, B. (Asian Journal of Chemistry, 2010)
Electrolysis in a specially designed W-shaped cell offers isolation of desired oxidation-reduction products after electrolysis of certain solutions of electrolytes. Oxidation and reduction of Ce, Co, Mn, Cr, V and other industrially important metal ion solutions has been successfully obtained and compared with the products obtained by conventional chemical methods. This method does not require elaborate and tedious chemical operations as encountered with conventional methods. It thus offers a simple and easy alternative for oxidation-reduction.